Periostin/Filamin-A: A Candidate Central Regulatory Axis for Valve Fibrogenesis and Matrix Compaction - Misra, Suniti; Ghatak, Shibnath; Moreno-Rodriguez, Ricardo A.; Norris, Russell A.; Hascall, Vincent C.; Markwald, Roger R. (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Background: Discoveries in the identification of transcription factors, growth factors and extracellular signaling molecules have led to detection of downstream targets that modulate valvular tissue organization that occurs during development, aging or disease. Among these, matricellular-protein, periostin, and cytoskeletal-protein filamin-A are highly expressed in developing heart valves. The phenotype of periostin-null indicates that periostin promotes migration, survival, differentiation of valve interstitial cushion cells into fibroblastic lineages necessary for postnatal-valve remodeling/maturation. Genetically inhibiting filamin-A expression in valve interstitial cushion cells mirrored the phenotype of periostin nulls, suggesting a molecular interaction between these two proteins resulted in poorly remodeled valve-leaflets that might be prone to myxomatous over time. We examined whether filamin-A has a cross-talk with periostin/signaling that promotes remodeling of postnatal heart valves into mature-leaflets. Results: We have previously shown that, periostin/integrin-β1 regulates Pak1 activation; here we revealed that the strong interaction between Pak1 and filamin-A proteins was only observed after stimulation of VICs with periostin; suggesting that periostin/integrin-β-mediated interaction between FLNA and Pak1 may have a functional role in vivo. We found that FLNA phosphorylation (S2152) is activated by Pak1, and this interaction was observed after stimulation with periostin/integrin-β1/Cdc42/Rac1 signaling; consequently FLNA binding to Pak1 stimulates its kinase activity. Our studies demonstrated that patients with floppy and/or prolapsed mitral valves, when genetically screened, were found to have point-mutations in the filamin-A gene at P637Q and G288R. Expression of either of these filamin-A-mutants failed to increase the magnitude of filamin-A (S2152) expression, Pak1-kinase activity, actin-polymerization and differentiation of VICs into mature mitral-valve-leaflets in response to periostin-signaling. Conclusion: PN stimulated bi-directional interaction between activated FLNA and Pak1 is essential for actin cytoskeletal reorganization and the differentiation of immature VICs into mature valve-leaflets.